A novel synthetic route to freely adjust the crystal structures of Ni-P compounds. (10th October 2016) - Xu, Hanghui; Lu, Shaoxiang; Ren, Lili
Abstract: Crystal-structure-controllable Ni-P compounds were synthesized using nickel chloride, nontoxic red phosphorus and polyethylene glycol. The hexagonal Ni2 P and tetragonal Ni12 P5 could be freely transformed via adjusting the amount of polyethylene glycol, and the mechanism of phase transformation was discussed. The catalytic performances of Ni-P compounds were promoted markedly with moderate quantity of PEG. However, excessive PEG will cover the active sites of catalysts and decrease the catalytic activity.